Pet Care Information System at Darussalam Pet Shop Based on Android: Sistem Informasi Perawatan Hewan Peliharaan Pada Darussalam Pet Shop Berbasis Android - Syafitri, Siti; Suendri, Suendri (Politeknik Ganesha Medan, 2023)
Modern technology has changed people's lifestyles, including how to raise pets. Pet is an animal kept at home or in a cage and exclusively cared for by its owner. Recently, more people owning pets. This had led to questions related to the hygiene and health of pets. An unkempt pet can cause problems for the owner, so numerous pet stores have emerged to help owners provide their animals with the care they require. However, many pet shops still use a manual system, which is considered ineffective for service, and utilizing information technology will make jobs easier while improving accuracy and information quality. Based on the problems described above, an application is required to assist and facilitate the pet shop itself and customers in caring for their pets. The research goal is to design and build suitable applications. In this journal, the researcher utilized both the Quantitative research methods and the Waterfall method for application development. For testing, the researcher used the Likert Scale. The Likert Scale calculation yielded a total score of 80.3 (Satisfied). Therefore, it can be concluded that the application is operating as intended and makes it easier to obtain pet-related information for user and manage schedules and incoming orders for administrators.